Fullerenol-tailored ionomer microenvironment for synergistic enhancement of proton exchange membrane fuel cell performance - Yongjian Su; Jinghao Zhou; Fangyuan Li; Zehao Tan; Enping Wang; Jiabin You; Guanghua Wei; Shuiyun Shen; Xiaohui Yan; Junliang Zhang (Science Bulletin, 2026)

Tuning of catalyst ink solids content to control colloidal structure and mitigate mass transport limitations in proton exchange membrane fuel cells - Yongjian Su; Cheng Yan; Congfan Zhao; Enping Wang; Jiewei Yin; Shuiyun Shen; Xiaohui Yan; Junliang Zhang (Chemical Engineering Journal, 2026)

Spatio-temporal ecological assessment of Camellia oleifera plantations using Sentinel-2 images based on deep learning - Yao Chen; Enping Yan; Shuyi Cao; Kaiqi Li; Dengkui Mo (International Journal of Remote Sensing, 2025)

A highly sensitive electrochemical immunosensor based on rGO-PEI-Ag nanocomposites for the detection of tilmicosin - Yumei Chen; Jialin Zhang; RuiRui Liu; Ying Zhang; Jingming Zhou; Hongliang Liu; Yankai Liu; Ke Yan; Yanhua Qi; Enping Liu; Xifang Zhu; Aiping Wang (Food Chemistry, 2024)

Monitoring of key Camellia Oleifera phenology features using field cameras and deep learning - Haoran Li.; Enping Yan; Jiawei Jiang; Dengkui Mo (Computers and Electronics in Agriculture, 2024)

Loss of GLTSCR1 causes congenital heart defects by regulating NPPA transcription - Fengyan Han; Beibei Yang; Yan Chen; Lu Liu; Xiaoqing Cheng; Jiaqi Huang; Ke Zhou; Dandan Zhang; Enping Xu; Maode Lai; Bingjian Lv; Hongqiang Cheng; et al. (Angiogenesis, 2023)
Precise and specific spatiotemporal domains of gene expression regulation are critical for embryonic development. Recent studies have identified GLTSCR1 as a gene transcriptional elongation regulator in cancer research. However, the function of GLTSCR1, especially in embryonic development, remains poorly understood. Here, we found that GLTSCR1 was essential for cardiac development because Gltscr1 knockout (Gltscr1 −/− ) led to embryonic lethality in mice with severe congenital heart defects (CHDs). Ventricular septal defect and double outflow right ventricular were also observed in neural crest cells with conditional deletion of Gltscr1, which were associated with neonatal lethality in mice. Mechanistically, GLTSCR1 deletion promoted NPPA expression by coordinating the CHD risk G allele of rs56153133 in the NPPA enhancer and releasing the transcription factor ZNF740-binding site on the NPPA promoter. These findings demonstrated that GLTSCR1 acts as a candidate CHD-related gene.

Construction of an infectious full-length and eGFP-tagged cDNA clone of a chilli ringspot virus isolate from Yunnan province, China - Mengying Hua; Shanshan Jiang; Enping Yuan; Qionglian Wan; Liyan Wang; Yuwen Lu; Hongying Zheng; Hairu Chen; Jianping Chen; Fei Yan; Shaoxiang Wang; Jiejun Peng (Archives of Virology, 2022)

Phenology-based classification of vegetation cover types in Northeast China using MODIS NDVI and EVI time series - Enping Yan; Guangxing Wang; Hui Lin; Chaozong Xia; Hua Sun (International Journal of Remote Sensing, 2015)